Corporate governance and sustainability - Chaudhury, Suman Kalyan (Discovery Pub. House, 2012)
Globalization of the marketplace has ushered in an era wherein the quality of corporate governance has become a crucial of survival of corporates. The compatibility of corporate governance practices with global corporate governance has, therefore, become a necessary pre-requisite for any corporation to manage effectively in the globalised market.